In response to crisis: the use of songs to respond to multiple crises in Yusuf Islam (Cat Stevens)' post-conversion lyrical compositions - Azwar Tahir (International Journal of Humanities and Innovation (IJHI), 2022)
Yusuf Islam, also known as Cat Stevens, is a well-known singer and songwriter. He had decided to avoid the music industry for many years. He focused more on humanitarian activism as well as building educational institutions in London. In 2006, through the release of the album entitled "An Other Cup", Stevens marked his return to popular music with a strong intention to carry his Islamic vision. Furthermore, he connected his humanitarian activism with his lyrical compositions. The artist has shown very intense participation in crises that happened across countries. In dealing with these crises, the use of a single seemed very rational since such crises need a fast response and a single song is easier to compose than an album. The result of those circumstances is Stevens' releasing several songs in response to multiple crises across different countries. He released "The Little Ones" to voice the misery of the genocide in Bosnia. Similarly, Islam released "Indian Ocean" for the victims of the tsunami in Indonesia, "My People" to support people's freedom regarding political turmoil in the Arab world, such as Egypt and Tunisia, and "He Was Alone" to show sympathy for children's refugees at the Syrian-Turkish border. These responses were all released in his post-conversion phase. This essay argues that Yusuf Islam, also known as "Cat Stevens," has used his post-conversion lyrics, particularly his singles, to help voice the misery of the victims of multiple crises.